Analysis of the Implementation of Airport Rescue and Fire Fighting Unit Operations in Efforts to Improve Aviation Security and Safety at Adi Soemarmo Boyolali International Airport - Adhen Mardhatilla Abinza; Aditya Dewantari (CV. Rayyan Dwi Bharata, 2023)
ARFF is a work unit that must exist at an airport. ARFF has three main tasks, namely operation, maintenance and training. The training aims to maintain the quality of ARFF personnel in dealing with unexpected events that we don't expect, maintenance aims to prepare the ARFF operating vehicle so that it is always ready when needed for operations, while operation is the culmination of what we do in training and maintenance. The role of the ARFF officer unit is to be responsible for operating and carrying out maintenance or maintenance of ARFF vehicles and handling emergencies at the airport. The purpose of this research is to find out the role of ARFF unit officers in supporting flight security and safety at Adi Soemarmo Boyolali Airport. In this research or study, researchers used qualitative research methods to collect data using observation, interview, and documentation techniques. The research was conducted from 1 February 2023 to 1 March 2023. Observations in this study involved efforts to increase flight security and safety by the Airport Rescue and Fire Fighting Unit at Adi Soemarmo Boyolali International Airport. ARFF Unit personnel at Adi Soemarmo Boyolali International Airport are the informants or respondents to the research interview activities. Documentation in this study involves recording activities in the work area of the ARFF Unit including the performance of the ARFF Unit and the ARFF Unit's efforts to improve flight security and safety at Adi Soemarmo Boyolali International Airport. The results of the study show that the level of flight security and safety carried out by the ARFF Unit at Adi Soemarmo Boyolali International Airport is trying to improve its performance at Adi Soemarmo Boyolali International Airport in order to maintain the level of flight security and safety.